2011
DOI: 10.1016/j.pain.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral indices of ongoing pain are largely unchanged in male mice with tissue or nerve injury-induced mechanical hypersensitivity

Abstract: Despite the impact of chronic pain on the quality of life in patients, including changes to affective state and daily life activities, rodent preclinical models rarely address this aspect of chronic pain. To better understand the behavioral consequences of the tissue and nerve injuries typically used to model neuropathic and inflammatory pain in mice, we measured home cage and affective state behaviors in animals with spared nerve injury (SNI), chronic constriction injury (CCI) or intraplantar CFA. Mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
182
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(205 citation statements)
references
References 62 publications
19
182
3
1
Order By: Relevance
“…Following CCI, rats exhibit abnormal posture of the injured hindpaw (toes held together and plantar-flexed and paw everted), as well as repeated shaking, guarding and licking of the injured hindpaw suggesting the presence of spontaneous pain 9 . In addition to sensory dysfunction, several investigators have shown that CCI evokes behavioural disabilities, such as disrupted social interactions, sleep disturbances, depressive-like and anxiety-like behaviours [10][11][12][13] , however this is in contrast to the failure to find such behavioural disabilities by others 14,15 . CCI is therefore commonly used to investigate both the pathophysiology, and potential therapeutic agents for treatment of neuropathic pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following CCI, rats exhibit abnormal posture of the injured hindpaw (toes held together and plantar-flexed and paw everted), as well as repeated shaking, guarding and licking of the injured hindpaw suggesting the presence of spontaneous pain 9 . In addition to sensory dysfunction, several investigators have shown that CCI evokes behavioural disabilities, such as disrupted social interactions, sleep disturbances, depressive-like and anxiety-like behaviours [10][11][12][13] , however this is in contrast to the failure to find such behavioural disabilities by others 14,15 . CCI is therefore commonly used to investigate both the pathophysiology, and potential therapeutic agents for treatment of neuropathic pain.…”
mentioning
confidence: 99%
“…It is noteworthy that several variations to the original procedure have been reported including using only 2 ligatures around the nerve 16,17 and using suture material other than chromic gut such as plain gut and polyglactin (vicryl) 18,19 in rats. In addition, the CCI model has also been modified for use in mice, where the procedure is identical, except for the use of 2-3 ligatures with various suture materials including chromic gut, nylon, and prolene 15,20,21 .…”
mentioning
confidence: 99%
“…Changes in activity and exploratory behaviours are common and have been noted in mice with cancer. For example, mice developing SL2 lymphoma spend less time rearing as disease progresses (van Loo et al, 1997). Other common changes include decreased food and water consumption (Jacobsen et al, 2013) which is often accompanied by weight loss, the most frequently measured parameter used to monitor laboratory animals (Dallman, 2000).…”
Section: Behavioural Changes In Mice With Diseasementioning
confidence: 99%
“…There are also likely to be considerable biomedical benefits to characterizing behavioural changes that occur with disease. There has been increasing concern about animal studies translating poorly to human patients with a contributing factor being that animal studies do not always sufficiently reflect disease in humans (van der Worp et al, 2010). Identification of the mouse models of disease that more closely replicate human disease phenotypes may improve their predictive validity (McGonigle and Ruggeri, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation